The Role of Volunteers in a Swimming Organization for Persons with Disabilities - Vernerova, Alena; Marova, Ivana; Chmelik, Frantisek (Healthcare, 2022)
Participation in leisure time physical activity (LTPA) has considerable health-related, psychological, and social benefits. However, the involvement of individuals with disabilities is considerably less than that of their peers without disabilities. A higher rate of participation of individuals with disabilities in LTPA may be achieved by the active involvement of volunteers. This study aimed to describe the importance of volunteer involvement in a swimming organization focused on individuals with disabilities, as perceived by all participants, including swimmers with disabilities, their parents, volunteers, and coaches. The organization uses volunteers as swimming instructors who work individually with swimmers with disabilities. The data were obtained through 11 semi-structured interviews with swimmers with disabilities and their parents, volunteers, and coaches. The interviews were transcribed verbatim and analyzed using a five-step inductive thematic analysis. As a result of the cooperation with the volunteer swimming instructors, swimmers with disabilities felt an improved range of movement, greater independence, and higher self-esteem than before they started using the services of the swimming organization. Consequently, even individuals with severe disabilities can participate in LTPA. Membership to the organization also provided space for the establishment of new social relations, and the instructors described them accepting persons with disabilities as their equals. More importantly, the involvement of volunteers enables organizations to provide respite care for parents.